Avverkning av sitkagranar i Skottland - Zackrisson, Arvid (2015)
The purpose of this study is to explain the problem with low growing branches on sitka spruce, making it hard to do timber harvesting in Scotland and how different forest equipment companies have solved the problem with solutions for a example a double pair of delimbing knives. This study is a part of the examination in the Forest Management Programme ( Bsc level) at the Swedish University of Agricultural Sciences located in Skinnskatteberg, Sweden. The scientific part of the study is about the biology, economy and using of the sitka spruce. And the result part is about the making of a small documentary film about sitka spruce harvesting in Scotland. Material to the film was assembled in Scotland in a location near Forth and within a radius of 200 kilometers. It took about four days to assembly all the material to the documentary film. To get the watchers more involved in the movie the scenes are filmed from different angles, attached to the harvester with small cameras, Go Pro. Some material is filmed from a further distance to get the beautiful surroundings caught on film. Difficulties in the making of the movie have been the weather with rain and strong winds, mounting the cameras on the harvester and keep they stuck despite wet and oily surface, and finally the need of using the daylight as much as possible because of the sensitive Go Pro cameras.